GIS as an educational tool: Mapping cultural sites in greek space-time - Galani, L.; Theodorakopoulou, K.; Skentos, A.; Kritikos, G.; Pavlopoulos, K. (Bulletin of the Geological Society of Greece, 2013)
This paper deals with the cartographical presentation of cultural succession in Greek space-time associated with core concepts of geographic and historical education. The pedagogic value of this study is to develop five distinct skills: sense of time-scale, historical and geographic comprehension, spatial analysis and interpretation, ability to perform geo-historical research, and procedure of geohistorical decision-making. The methodology is based on the calibration of a set of criteria for each cultural site that covers the topics of economy, geomorphology, society, religion, art and science. Further analysis of these data forms a geodatabase. In addition, palaeogeographic and historical maps of the cultural sites derived by the geodatabase provide information about temporal and spatial changes. As result, students will be able to develop a multidimensional and interdisciplinary approach, in order to reconstruct the evolution of the site.